Penerapan Hukum Terkait Pembagian Harta Gono-Gini Akibat Perceraian - Patahillah Asba; Herman Balla; Ismail Candra; Johamran Pransisto (Jurnal Litigasi Amsir, 2022)
This study aims to determine the application of law related to the division of gono gini property after divorce in case decision No. 273/Rev.G/2019/PA. Sidrap. This research uses a normative-empirical type of legal research. The results of the study showed that the application of the law related to the division of gono gini property after divorce in general and based on the judgment of case No. 273/Rev.G/2019/PA. Sidrap in particular, where in the concept of common property there are several binding principles, namely 1. Property acquired during marriage; 2. Not looking at whose side is working, whether it is husband or wife; 3. Do not question on whose behalf the property or goods are; 4. Each party's share of the common property is half of the total property so long as during the marriage both parties carry out their respective obligations; 5. Mixing.property.acquired either by husband.wife.as long as.the marriage is lived into common property (property.syirkah) can be excluded in a marriage agreement (huwelijke voorwaarden).